Lactobacillus plantarum KFY02 enhances the relieving effect of gardenoside on montmorillonite induced constipation in mice. Issue 17 (11th March 2020) - Mu, Jianfei; Zhao, Xin; Zalan, Zsolt; Hegyi, Ferenc; Takács, Krisztina; Du, Muying
Abstract : Lactobacillus plantarum KFY02 (KFY02), isolated from naturally fermented milk yoghurt in Korla, Xinjiang, Northwest of China, showed gardenoside action for the intestinal regulation of constipated mice. Abstract : Lactobacillus plantarum KFY02 (KFY02), isolated from naturally fermented milk yoghurt in Korla, Xinjiang, Northwest of China, showed gardenoside action for the intestinal regulation of constipated mice. Comparatively, the effects of KFY02 (0.5 × 10 8 CFU kg −1, by body weight (BW)), gardenoside (50 mg kg −1, BW), and KFY02 (0.5 × 10 8 CFU kg −1, BW) + gardenoside (50 mg kg −1, BW) on intestinal regulation in mice with montmorillonite-induced constipation were also studied. Enzyme linked immunoassay, hemotoxylin and eosin (H&E) staining, quantitative polymerase chain reaction (qPCR) assay and high performance liquid chromatography (HPLC) analysis were used for the study. Compared with the model group, KFY02 + genipin (combined group) increased the propelling rate of activated carbon in the small intestines of mice and accelerated the discharge of the first black stool in mice. At the same time, the combination group reduced the levels of motilin (MTL), substance P (SP) and endothelin-1 (ET-1) in the serum, and increased the somatostatin (SS), vasoactive intestinal peptide (VIP), acetylcholinesterase (AchE) and gastrin (Gastrin) levels in the serum, which made these parameters close to those of the normal group. Using qPCR analysis, it was observed that the combined group up-regulated the mRNA expression of endothelial nitric oxide synthase (eNOS), stem cell factor (SCF), stem cell factor receptor (c-Kit), glutathione (GSH), catalase and manganese-superoxide dismutase (Mn-SOD) and down-regulated the expression of inducible nitric oxide synthase (iNOS) and transient receptor potential vanilloid receptor 1 (TRPV1). The combination increased the Bacteroides and Akkermansia abundances and decreased the Firmicutes abundance in the feces of the constipated mice and decreased the Firmicutes / Bacteroides ratio. The expression of the above genes was similar to that of the normal group. The results indicate that KFY02 produced β-glucosidase to hydrolyze the gardenoside glycosidic bond to produce genipin and can effectively promote the regulation of gastrointestinal hormones and intestinal peristalsis and reduce oxidative tissue damage in constipated mice. This study also confirmed that KFY02 has similar relieving effects to gardenoside for constipation in mice.